2014
DOI: 10.1007/s00737-013-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in early pregnancy: prevalence and contributing factors

Abstract: Antenatal anxiety symptoms are not only a health problem for the expectant mother. Research has found that maternal anxiety may also have an impact on the developing baby. Therefore, it is important to estimate the prevalence of maternal anxiety and associated factors. The current study aims to estimate the prevalence of anxiety symptoms during the first trimester of pregnancy and to identify associated risk factors. Secondly, to investigate other factors associated with anxiety during early pregnancy includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
2
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 38 publications
11
183
2
17
Order By: Relevance
“…Nearly 20%-40% of pregnancies are complicated by adverse intrauterine conditions, including maternal mental health disorders, diabetes, obesity, and preeclampsia (Ananth et al, 2013;Bennett et al, 2004;Dawson et al, 2015;DeSisto et al, 2014;Goodman et al, 2014;Rubertsson et al, 2014). These fetal exposures are significant risk factors for neuropsychiatric disease predisposition, in particular in male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 20%-40% of pregnancies are complicated by adverse intrauterine conditions, including maternal mental health disorders, diabetes, obesity, and preeclampsia (Ananth et al, 2013;Bennett et al, 2004;Dawson et al, 2015;DeSisto et al, 2014;Goodman et al, 2014;Rubertsson et al, 2014). These fetal exposures are significant risk factors for neuropsychiatric disease predisposition, in particular in male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…For each item, we assigned a score of 0, 1, 2, and 3, to the response categories of 'not at all', 'several days', 'more Authors obtained the total by adding together the scores for the nine questions. With a possible total score of 27, patients were classified as absence of depression (PHQ-9 score: 0-4), mild depression (PHQ-9 score: 5-9), moderate depression (PHQ-9 score: 10-14), moderately severe depression (PHQ-9 score: 15-19), or severe depression (PHQ-9 score: [20][21][22][23][24][25][26][27]. At the end of it all, patients who scored ≥10 suggestive of anxiety as well as depressive disorders were referred for appropriate psychiatric care.…”
Section: Methodsmentioning
confidence: 99%
“…20 Rubertsson et al reported depression and anxiety in early pregnancy to be associated with the risk for preeclampsia. 21 Kharaghani et al in Tehran, Iran reported the prevalence of moderate to severe depression in preeclamptic women as 31.2% during pregnancy. 22 In order to document the perinatal frequency of anxiety and depression disorders in women with hypertensive pregnancy disorders in our setting, we decided to carry out this study.…”
mentioning
confidence: 99%
“…Anxiety symptoms (AS) during pregnancy have an international prevalence between 9.1% and 15.6% (Fadzil et al, 2013;Rubertsson et al, 2014) and a prevalence between 10% and 15% in Mexico (Ceballos-Martínez et al, 2010;Navarrete et al, 2012). Occasionally, AS during pregnancy are more frequent than depressive symptoms (DS) (Navarrete et al, 2012).…”
Section: Introductionmentioning
confidence: 99%